Fire Retardancy Properties and Thermal Degradation of Three Timber Species Overlayed by Sengon Wood Charcoal - Joko Sulistyo; Sri Nugroho Marsoem; Tomy Listyanto; Yus Andhini Bhekti Pertiwi Bhekti Pertiwi (Jurnal Ilmu Kehutanan)
Wood as biomaterial poses unfavorable property that is wood can burn. Fire disaster in wooden houses threaten human lifes. Efforts have been implemented to improve fire retardancy properties of timbers for wooden houses. This research was carried out to develop carbon-based fire-retardant materials (CFR) overlay on three timber species. The effectiveness of carbon-based fire-retardant material from sengon charcoal to improve fire resistance in teak, red meranti and pine timbers was studied. The CFR materials were prepared by mixing 10 mesh sengon charcoal powder and PVAC adhesive with a ratio (w/w) 0f 60:40 followed by a hot pressing at a temperature of 80 °C with a pressure of 70 MPa for 15 minutes resulting 4 mm x 18 cm x 18 cm carbon sheets. Teak, red meranti and pine timbers overlayed by CFR sheet from sengon charcoal were tested through feeding on fire for 1500 seconds based on ASTM E 6-02 method with a modification. CFR sheets from sengon charcoal were effective to improve the fire resistance of the three species of timbers. CFR overlayed on timber surface was functioned as solid barrier material which was able to block thermal from fire and protected timber from thermal degradation showing by lesser percentage of cross section unburning area on teak CFR i.e. 68.6% than that of teak control i.e. 57.9%, lower percentage of weight loss on pinus CFR and red meranti CFR i.e. 50.56% and 26.57% respectively comparing with the controls i.e. 76.98% and 30.72%, and similar values of weight change percentage between teak CFR and red meranti CFR with the control until 700-1,160 s.